Malignant Peritoneum Mesothelioma with Hepatic Involvement: A Single Institution Experience in 5 Patients and Review of the Literature - Shan-shan Su; Guo-qi Zheng; Ya-gang Liu; Yue-feng Chen; Zhao-wei Song; Shu-jing Yu; Ning-ning Sun; Yu-xin Yang (Gastroenterology Research and Practice)
Malignant peritoneal mesothelioma with invasion of the liver is an invariably fatal disease. We aimed to clarify the characteristics of malignant peritoneal mesothelioma cases with liver involvement. The clinical presentation, computed tomography images, and immunohistochemical and histopathological features of 5 patients with malignant peritoneal mesothelioma and liver involvement were evaluated. The diagnosis was established by imaging and immune profiles of the tumours. A review of 8 cases with primary or invading malignant mesothelioma in liver is presented. All 5 mesothelioma cases were asbestos-related. CT images of malignant peritoneal mesothelioma with the liver involvement typically showed that the lesion grew inside the liver along the capsule and was possibly accompanied by capsule breakthrough and extrahepatic infiltration. The tumours exhibited a common epithelioid appearance in all 5 patients and most cases revealed positive Cal, CK, and MC with negative CEA and HeP. Different from our findings, the review of literature revealed that most malignant mesothelioma of liver was due to primary intrahepatic malignant mesothelioma. Finally, we concluded that the diagnosis of malignant peritoneal mesothelioma cases with liver invasion is reliably achieved by the history of asbestos exposure, the characteristic CT imaging, and immune profiles of the tumours.